(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
India’s nominal gross domestic product (GDP) at current prices is estimated at Rs. 232.2 trillion(US 3.1 trillion) in 2021-22. India’s trade and external sector had a significant impact on the GDP growthand expansion in per capita income. India’s overall exports (Merchandise and Services combined) inApril-March 2021-22 are estimated to be US 669.7 billion, witnessing a growth of 34.5 over the sameperiod last year and an increase of 27.2 over April to March 2019-20. India has been able to beat theoverall export target of US 650 billion despite the global economic slowdown caused by the Covid-19pandemic and the recent geopolitical developments in Europe. As the pandemic receded, Indiawitnessed a revival in domestic demand resulting in strong import growth. During the year 2021-22,India’s overall imports (Merchandise and Services combined) are estimated to be US 756.7 billion,growing 47.8 over the same period last year and 25.5 over the year 2019-20, crossing the prepandemiclevel. China, UAE, and the USA were the largest import sources for India.